The Strategies Adopted by the Primary School Administrators in Removing the Deficiencies Related to the Education Training State of the Schools - Demirtaş, Zülfü; Kahveci, Gökhan (Pamukkale Üniversitesi, 2015)
This study aimed to define the strategies adopted by primary school principals in order to carry out the recommendations under the “education state” title in inspection notification. 37 administrators have voluntarily participated in the study as 9 of them are school principals and 28 of them are assistant principals Unstructured interview form is used in the study and “What kind of strategies do you pursue to carry out the recommendations made for arranging education-training state of your school?” question is directed at participants. Data are analyzed through qualitative techniques such as content analysis. According to the findings of the study primary school administrators adopted four main strategies in order to remove deficiencies in the education state of their schools as: (1) Attendance and cooperation (2) Social, cultural and sportive activities (3) Convenience with the regulations (4) Guidance services.

Bu araştırma, ilköğretim okulu yöneticilerinin denetim tebliğinde yer verilen “eğitim ve öğretim durumu” başlığı altında yer alan önerileri yerine getirmede izledikleri stratejileri belirlemek amacıyla yapılmıştır. Araştırmaya gönüllü olarak dokuz okul müdürü ve 28 müdür yardımcısı olmak üzere toplam 37 okul yöneticisi katılmıştır. Araştırmada yapılandırılmamış görüşme formu kullanılmış olup katılımcılara “Okulun eğitim-öğretim durumunu düzenleme konusunda yapılan önerileri yerine getirmede ne gibi stratejiler izlersiniz?” sorusu yöneltilmiştir. Elde edilen veriler nitel teknikler kullanılarak analiz edilmiştir. Araştırma bulgularına göre, ilköğretim okulu yöneticilerinin okulun eğitim öğretim durumu ile ilgili eksiklikleri gidermede (1) Katılım ve İşbirliği, (2) Sosyal, Kültürel ve Sportif Etkinlikler, (3) Mevzuata Uygunluk ve (4) Rehberlik Hizmetleri olmak üzere dört temel strateji izledikleri belirlenmiştir.
İlköğretim Okulu Yöneticilerinin Okullarında Eğitim Öğretim Durumu ile İlgili Eksikliklerin Giderilmesinde İzledikleri Stratejiler